7-Nitro-1,2,3,4-tetrahydronaphthalene-1-spiro-2′-(1,3-dithiane) - Fun, Hoong-Kun (International Union of Crystallography, 2009)
In the title compound, C(13)H(15)NO(2)S(2), the nitro group is coplanar with the benzene ring to which it is attached, forming a dihedral angle of 1.07 (14)°. The dithiane ring adopts a chair conformation. In the crystal structure, molecules are linked through C—H⋯O and C—H⋯π [C⋯Cg = 3.7164 (15) Å] interactions. The crystal studied was an inversion twin with an 0.134 (5):0.866 (5) domain ratio.